Resistance of Moroccan wheat lines against the root-lesion nematode Pratylenchus thornei - Lasali, Salah-Eddine; Mokrini, Fouad; Ferrahi, Moha; Iraqi, Driss; Udupa, Sripada M.; Lahlali, Rachid; Dababat, Abdelfattah A.S. (Organization of Nematologists of Tropical America, 2024)
The root lesion nematode, Pratylenchus thornei, causes high yield losses in rainfed wheat fields in Morocco, as well as worldwide. Growing resistant varieties is one of the most effective methods for controlling nematodes. Therefore, a collection of 69 wheat lines (Triticum aestivum and T. durum), provided by the National Institute of Agricultural Research (INRA-Meknes, Morocco) and the International Center for Agricultural Research in the Dry Areas (ICARDA-Rabat, Morocco), were screened for resistance to P. thornei in tubes (15 x 20 x 120 mm(3)) under greenhouse conditions. The resistance level was evaluated based on the number of nematodes extracted from roots and soil 9 weeks after infestation. Three lines, L3 (DW-37), L14 (DW-37), and L54 (USG3535), were found to be moderately resistant (Reproduction factor <1) to P. thornei.